Alexia Without Agraphia: A Rare Entity - Rupareliya, Chintan (Cureus, 2017)
Pure alexia refers to an acquired disorder associated with the damage to medial occipitotemporal gyrus in the dominant hemisphere, which is also known as visual word form area (VWFA). VWFA is involved in rapid word recognition and fluent reading. Alexia without agraphia is a disconnection syndrome that occurs when the splenium is also damaged with the occipital lobe on a dominant side. We report a case of a 72-year-old right-handed male who presented with alexia without agraphia accompanied by right homonymous hemianopia resulting from acute infarct of the left occipital lobe, the splenium of the corpus callosum and posterior thalamus that probably occurred on the previous day. During the evaluation, he exhibited marked impairment in the ability to read with the vision being grossly normal. Magnetic resonant imaging (MRI) revealed an acute infarct of the left occipital lobe, the splenium of the corpus callosum and posterior thalamus. A computerized tomography angiogram (CTA) revealed left posterior cerebral artery (PCA) territory infarct without any evidence of hemorrhagic conversion. Infarction of the occipital lobe on the dominant side (left) in a right-handed individual may cause a disruption in the visual word form area and is manifested by an inability to read with no abnormalities in visual acuity.